Genomic and clinicopathological features of lung adenocarcinomas with micropapillary component - Li, Peng; Liu, Lu; Wang, Dong; Yang, Ronghua; Xuan, Yunpeng; Han, Yudong; Wang, Jinglong; Guo, Lijie; Zhang, Liwen; Zhang, Shanshan; Wang, Yongjie (Frontiers in Oncology, 2022)
Background: Lung adenocarcinoma with a micropapillary component (LAMPC) is a histological subtype of lung cancer that has received increasing attention due to its correlation with poor prognosis, and its tendency to recur and metastasize. At present, comprehensive genomic profiles and clinicopathological features for LAMPC remain unclear and require further investigation. Methods:A total of 465 LAMPC patients were recruited and divided into four groups according to MPC proportions, and the correlations between varying proportions of MPCs and clinicopathological characteristics were analyzed. 29 LAMPC patients and 89 non-MPC that had undergone NGS testing were selected for determine comprehensively analyze genomic variations and the difference between LAMPC and MPC. Gene alterations of LAMPC between Chinese and Western populations were also compared using cBioPortal data. Results: A higher proportion of MPCs, associated with higher tumor stage, pleural invasion, and vascular tumor thrombus formation. Compared to non-MPC patients, LAMPC patients have a lower frequency of SNVs and a higher frequency of insertion-deletion mutations. Mutations in TP53, CTNNB1, SMAD4, and ALK were significantly more frequent in LAMPC patients. ERBB2 mutations were only detected in non-MPC patients. Gene mutations in the Wnt pathway were significantly more common in LAMPC patients as compared to non-MPC patients. ALK fusions were more prevalent in younger patients. Patients with KRAS or LBP1B mutations had larger tumor diameters than patients with their wild-type. Patients with KRAS mutations were more likely to develop vascular tumor thrombus. We determined that mutations in EGFR were significantly higher in Chinese patients than in a MSKCC Western cohort. ALK fusions were exclusively detected in the Chinese cohort, while mutations in KEAP1 and NOTCH4 were only detected in the MSKCC cohort. Wnt pathway gene mutations were significantly higher in the Chinese cohort. Conclusion: LA patients with higher proportions of MPCs were determined to have a higher tumor stage, pleural invasion, and vascular tumor thrombosis formation. We comprehensively analyzed the genomic mutation characteristics of LAMPC patients and identified multiple, novel MPC-related gene alterations and pathway changes. Our data provide further understanding of the nature of the LAMPC and potential drug-targeted gene alterations, which may lead to new therapeutic strategies.